Risk analysis, dam safety, dam security and critical infrastructure management - International Forum on Risk Analysis, Dam Safety, Dam Security and Critical Infrastructure Management (3IWRDD-FORUM), (3rd : 2011, October : Valencia, Spain); Escuder-Bueno, Ignacio (Leiden, The Netherlands : CRC Press, 2012)
Includes bibliographical references and index